“The best thing is that you are doing it for yourself” – perspectives on acceptability and feasibility of HPV self-sampling among cervical cancer screening clients in Tanzania: a qualitative pilot study - Aleksandra Bakiewicz; Vibeke Rasch; Julius Mwaiselage; Ditte S. Linde (BMC Women's Health, 2020)
Abstract Background Cervical cancer is the most common type of cancer in sub-Saharan Africa, and it is also the cancer disease that most women die from. The high mortality rate is partly due to low attendance rates to screening services and low sensitivity of visual inspection with acetic acid, which is the standard screening method used in screening programs in sub-Saharan Africa. In order to overcome of the burden of disease new screening strategies and methods are warranted. This study aims to explore the acceptability and feasibility of HPV self-sampling compared to provider-based sampling among cervical cancer screening clients living in Dar es Salaam. Methods Women attending cervical cancer screening at Ocean Road Cancer Institute in Dar es Salaam, Tanzania between February – April 2017 were invited into the study. The participants had (1) a provider-collected sample, and (2) a self-sample for HPV on top of the regular cervical cancer screening. 50% of the participants conducted the self-sample after receiving a written instruction guide of how to collect the sample (written). The other 50% received both the written and an oral introduction to self-sampling (written+). All participants could ask for nurse assistance during self-sample collection if needed. Individual semi-structured interviews were conducted with the participants post sample collection. Data collection stopped when saturation was reached. Data were analysed using a thematic content analysis. Results Twenty-one women participated in the study. Regardless of how women were introduced to the self-sample (written or written+), there was a high demand for nurse presence as they felt uncertain of their personal capabilities to collect the self-sample correctly. However, as long as nurse assistance was an option most women perceived self-sampling as easy and comfortable though few experienced bleeding and pain. The majority of women preferred self-sampling over provider-sampling primarily due to the method being more private than the provider-sampling. Conclusions HPV self-sampling was well-perceived and accepted, however, for the method to be feasible a nurse needed to be present. HPV Self-sampling may be an alternative method to increase uptake of cervical cancer screening. Larger quantitative studies are recommended to support the study findings.